Learning network penetration testing with Kali Linux - Gradisteanu, Cristian (Packt Publishing, 2017)
"Learn how to test your network against various types of attacks. We will teach viewers how to install Kali Linux, discuss about different phases of pen testing, etc. By the end of this section you will become familiar with the tools that Kali Linux offers to perform network penetration testing, how to exploit the vulnerable systems and how to patch them."--Resource description page